Shape–Trait Consistency: The Matching Effect of Consumer Power State and Shape Preference - Yao, Feng; Jin, Xiaotong; Wu, Banggang; Zhao, Taiyang; Ma, Tiannv (Frontiers in Psychology, 2021)
Angular and rounded shapes are two important visual elements, widely used in the design of product shapes and brand logos. By introducing the power state, a psychological variable that is inherently relevant to consumers' product choices, brand preferences, and decision-making, we propose that consumers’ power state influences their shape preference. Specifically, compared to low-power consumers, high-power consumers respond more positively to angular, as opposed to rounded shapes, because the angular shape facilitates the expression of competence (as opposed to warmth). Through four studies, we provide consistent support for our main predictions as well as the underlying processes. Studies 1 and 2 demonstrate that consumers experiencing higher power are more likely to prefer an angular shape over a rounded shape than those experiencing lower power through different research methods, research objects, and experimental materials. On this basis, studies 3 and 4 further explore the mechanisms underlying the observed effects. These findings contribute to sensory marketing and power research and provide important implications for visual design and advertisement development.